The Influence of Reciprocal Teaching Style on Volleyball Smash Learning Outcomes - Fajar Mugo Raharjo; Agung Nugroho; Ahmad Al Munawar (Jurnal Pendidikan Jasmani (JPJ), 2020)
This study aims to determine the improvement of Smash learning outcomes in volleyball games through reciprocal teaching styles in X students of the Private High School of Dharma Karya in the 2015/2016 school year. The subjects in this study were class X with 32 students. This study uses the Experimental method, After the data is collected and analyzed, the results of the analysis are obtained: (1) from the data of the Pre-test learning results obtained 20 people (62.5%) who have reached the level of mastery learning, while 12 people (37.5 %) has not reached the level of mastery learning. With an average value of student learning outcomes is 64.4. (2) 28 students (87.5%) of the pre-test achievement test results have reached the level of mastery learning, while 4 people (12.5%) have not reached the level of mastery learning, with an average value of student learning outcomes is 78 , 1. In this case it can be seen that an increase in the average value of student learning outcomes from pre-test to pre-testI is an increase in classical completeness by 25%. Based on the results of data analysis, it can be said that through reciprocal teaching styles increases the learning outcomes of Smash in volleyball games for students of the Private High School of Dharma Karya in the 2015/2016 school year.